Dose-Response Thresholds for Progressive Diseases - Louis Anthony (Tony) (SAGE Publishing, 2012)
Many diseases, including cancers, heart diseases, and lung diseases, can usefully be viewed as arising from disruption of feedback control systems that normally maintain homeostasis of tissues and cell populations. Excessive exposure can destabilize feedback control loops, leading to sustained elevation of variables to saturated levels and clinical consequences such as chronic unresolved inflammation, destruction of tissue (as in emphysema), proliferation of cell populations (as in lung cancer), and increases in reactive oxygen species and protease levels (as in coronary heart diseases and chronic obstructive lung disease). We propose a framework for understanding how exposure can destabilize normally homeostatic feedback control systems and create sustained imbalances and elevated levels of disease-related variables, by creating a new, locally stable, alternative equilibrium for the dynamic system, in addition to its normal (homeostatic) equilibrium. The resulting model, which we call alternative-equilibria (AE) theory, implies the existence of an exposure threshold below which transition to the alternative equilibrium (potential disease) state will not occur. Once this threshold is exceeded, progression to the alternative equilibrium continues spontaneously, even without further exposure. These predictions may help to explain patterns observed in experimental and epidemiological data for diseases such as COPD, silicosis, and inflammation-mediated lung cancer.